Pengaruh Penguasaan Ilmu Nahwu Dan Sharaf Terhadap Kemampuan Membaca Kitab Fathul Qarib - Muhamad Bisri Ihwan; Sumari Mawardi; Ulin Ni’mah (Institut Agama Islam Darusssalam Blokagung, 2022)
The purpose of this research was to determine the effect of mastery of nahwu and sharaf on the ability to read the book of Fathul Qarib. The research method used in this study is a quantitative method. Data analysis was carried out with correlational data that had been collected. The data consists of the independent variable (X), namely the mastery of nahwu and sharaf. And the dependent variable (Y), namely the ability to read the book Fathul Qarib. Based on the results of data analysis conducted by researchers, it can be concluded that: mastery of nahwu shorof science has a very good value, ability to read the book of Fathul Qorib has a fairly good value, there is a close relationship between mastery of nahwu and shorof science with ability to read the book of Fathul Qorib, and there is a significant positive effect between mastery of nahwu and shorof science with the ability to read the book of Fathul Qorib by 22.73% and there are still 77.27% other things that affect the Y variable.